METHODOLOGY FOR ORGANIZING AND ASSESSING INDEPENDENT CREATIVE WORK IN TEACHING LANDSCAPE COMPOSITION - Murodova Shohinabonu Alisher qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article examines methodologies for organizing and assessing students’ independent creative work in landscape composition lessons. The study highlights approaches that promote self-directed learning, creativity, and technical proficiency. By implementing project-based assignments, rubrics, and reflective assessment, teachers can enhance students’ engagement, foster critical thinking, and improve both compositional and color skills. Findings indicate that structured guidance combined with autonomous tasks supports the development of artistic competencies while encouraging individual expression.